Global nursing in an Ebola viral haemorrhagic fever outbreak: before, during and after deployment - Eva von Strauss; Stéphanie Paillard-Borg; Jessica Holmgren; Panu Saaristo (Taylor & Francis Group, 2017)
Background: Nurses are on the forefront and play a key role in global disaster responses. Nevertheless, they are often not prepared for the challenges they are facing and research is scarce regarding the nursing skills required for first responders during a disaster situation. Objectives: To investigate how returnee nursing staff experienced deployment before, during and after having worked for the Red Cross at an Ebola Treatment Center in Kenema, West Africa, and to supply knowledge on how to better prepare and support staff for viral haemorrhagic fever outbreaks. Methods: A descriptive, cross-sectional approach. Questionnaires were administered to nurses having worked with patients suffering from Ebola in 2014 and 2015. Data collection covered aspects of pre-, during and post-deployment on clinical training, personal health, stress management, leadership styles, socio-cultural exposure and knowledge transfer, as well as attitudes from others. Data was analysed using both quantitative and qualitative methods. Results: Response-rate was 88%: forty-four nurses from 15 different countries outside West Africa answered the questionnaire. The respondents identified the following needs for improvement: increased mental health and psychosocial support and hands-on coping strategies with focus on pre- and post-deployment; more pre-deployment task-oriented clinical training; and workload reduction, as exhaustion is a risk for safety. Conclusions: This study supplies knowledge on how to better prepare health care staff for future viral haemorrhagic fever outbreaks and other disasters. Participants were satisfied with their pre-deployment physical health preparation, whereas they stressed the importance of mental health support combined with psychosocial support after deployment. Furthermore, additional pre-clinical training was requested.